Different photosynthetic inorganic carbon utilization strategies in the heteroblastic leaves of an aquatic plant Ottelia ovalifolia - Liao, Zuying; Li, Pengpeng; Zhou, Jingzhe; Li, Wei; Jiang, Hong Sheng (Frontiers in Plant Science, 2023)
Abstract: The leaves of the heteroblastic aquatic plant Ottelia ovalifolia faces submerged and aerial environments during its life history. However, the acclimation of the submerged leaves and floating leaves to these two environments in morphology, physiology, and biochemistry remain unclear. In the present study, we investigated the acclimation of the CO2-concentrating mechanisms in these two types of leaves. We found that the submerged leaves were longer, narrower, and thinner than the floating leaves, which increased the specific surface area of the leaves and lead to better absorption of the inorganic carbon underwater. Meanwhile, the floating leaves absorbed atmospheric CO2 directly through the stomata to acclimate to the aerial environment. Both the leaf types had the ability to use HCO3-, but the capacity in submerged leaves was stronger than that in floating leaves. The extracellular carbonic anhydrase and anion exchanger were responsible for the HCO3- use in both types of leaves. The higher ratio of chlorophyll a/b and content of anthocyanin in floating leaves than that in submerged leaves indicated that the acclimation of aerial and submerged photosynthesis depended on changes in the photosynthetic pigments. Based on the stable carbon isotope ratio, key enzyme activities of the C4 pathway indicated that submerged leaves might have the ability to perform C4 metabolism while floating leaves only performed C3 metabolism. In summary, O. ovalifolia acclimates to submerged and aerial environments through changes in morphology, physiology, and biochemistry during different growth stages.